Multimodal image reconstruction from tomographic diffraction microscopy data. (19th July 2022) - Abbessi, Riadh; Verrier, Nicolas; Taddese, Asemare Mengistie; Laroche, Steve; Debailleul, Matthieu; Lo, Mohamed; Courbot, Jean‐Baptiste; Haeberlé, Olivier
Summary: Tomographic diffraction microscopy (TDM) is a tool of choice for high‐resolution, marker‐less 3D imaging of biological samples. Based on a generalization of digital holographic microscopy with full control of the sample's illumination, TDM measures, from many illumination directions, the diffracted fields in both phase and amplitude. Photon budget associated to TDM imaging is low. Therefore, TDM is not limited by phototoxicity issues. The recorded information makes it possible to reconstruct 3D refractive index distribution (with both refraction and absorption contributions) of the object under scrutiny, without any staining. In this contribution, we show an alternate use of this information. A tutorial for multimodal image reconstruction is proposed. Both intensity contrasts and phase contrasts are proposed, from the image formation model to the final reconstruction with both 2D and 3D rendering, turning TDM into a kind of 'universal' digital microscope.